ANALISIS PENERIMAAN PAJAK REKLAME KABUPATEN MAGELANG DENGAN PENDEKATAN VECM PERIODE 2010 - 2014 - Mardiana, Lisa Dwi; Prawoto, Nano (Jurnal Ekonomi & Studi Pembangunan, 2016)
The objectives of this research are to analyze the influence of PDRB, the number of SIUP and industries towards the advertisement tax revenues in District of Magelang. The data used in this research are monthly-secondary data which is taken from the data in 2010:M08-2014:M12. Analysis model used in this research is regression model VECM using the assistance of software EVIEWS 7.2. VECM model is chosen in this research since it is hoped to be able to explain behavioral research variables in the long-term. Moreover, variable of PDRB and the number of SIUP have influence towards the advertisement tax revenues in District of Magelang. PDRB and the number of SIUP have stability connection or in balance and the same movement in long-term. In other words, they, in any short-term period, are likely to adjust to each other in order to achieve long-term equilibrium. At the same time, the number of industries has no any influences towards the advertisement tax revenues because not all industries located in the District of Magelang put up the advertisement to promote goods or services.